Regulation and Characterization of a Newly Deduced Cell Wall Hydrolase Gene (cwlJ) Which Affects Germination of Bacillus subtilis Spores - Ishikawa, Shu (American Society for Microbiology, 1998)
The predicted amino acid sequence of Bacillus subtilis ycbQ (renamed cwlJ) exhibits high similarity to those of the deduced C-terminal catalytic domain of SleBs, the specific cortex-hydrolyzing enzyme of B. cereus and the deduced one of B. subtilis. We constructed a cwlJ::lacZ fusion in the B. subtilis chromosome. The β-galactosidase activity and results of Northern hybridization and primer extension analyses of the cwlJ gene indicated that it is transcribed by Eς(E) RNA polymerase. cwlJ-deficient spores responded to both l-alanine and AGFK, the A(580) values of spore suspensions decreased more slowly than in the case of the wild-type strain, and the mutant spores released less dipicolinic acid than did those of the wild-type strain during germination. However, the mutant spores released only slightly less hexosamine than did the wild-type spores. In contrast, B. subtilis sleB spores did not release hexosamine at a significant level. While cwlJ and sleB spores were able to germinate, CJSB (cwlJ sleB) spores could not germinate but exhibited initial germination reactions, e.g., partial decrease in A(580) and slow release of dipicolinic acid. CJSB spores became slightly gray after 6 h in the germinant, but their refractility was much greater than that of sleB mutant spores. The roles of the sleB and cwlJ mutations in germination and spore maturation are also discussed.